Intercultural Sensitivity for Bullying Prevention in Multiethnic Classrooms: A Cultural Study at Sembilanbelas November University - Syam, Hariadi; Dollah, Syarifuddin (Universitas Pahlawan Tuanku Tambusai, 2026)
Bullying in multiethnic classrooms remains a persistent challenge, particularly in educational settings where cultural diversity is not always supported by strong intercultural understanding. Previous studies have widely emphasized the importance of intercultural sensitivity for promoting inclusive learning environments; however, there is limited empirical research that examines how intercultural sensitivity is experienced and enacted in everyday classroom interactions as a mechanism for bullying prevention in higher education contexts. This study aims to explore how intercultural sensitivity contributes to bullying prevention within the culturally diverse classrooms of Universitas Sembilanbelas November Kolaka. Using a qualitative research design, data were collected through in depth interviews with students and lecturers from multiple ethnic backgrounds. The findings reveal that intercultural sensitivity supports bullying prevention by reducing stereotyping, enhancing empathy, and encouraging more respectful and constructive peer interactions. The study concludes that strengthening intercultural sensitivity is a crucial cultural approach for fostering safer and more inclusive multiethnic classroom environments.